KUALITAS PELAYANAN, KEPUASAN, DAN LOYALITAS NASABAH: APLIKASI SERVQUAL MODEL PADA LEMBAGA KEUANGAN MIKRO SYARIAH KOTA MALANG - Hastuti, Tuti; Nasri, Muhammad (JURNAL MANAJEMEN DAN AKUNTANSI, 2014)
This study aims at: (i) analyzing the direct effect of service quality on customer satisfaction; (ii) analyzing the direct effect of service quality on customer loyalty (iii ) analyzing the direct effect of customer satisfaction on customer loyalty; (iv) Testing empirically the factors of service quality wich is influential in the process of customer loyalty throught customer satisfaction. This study is a survey research -type explanations. The samples used are 112 respondents as clients of Microfinance Institutions Sharia (LKMS) Malang. Sampling techniques of purposive sampling . Statistical analysis path analysis.The results: (i) quality of service a significant effect on customer satisfaction , while the dimensions of tangibles and empathy has no effect on customer satisfaction and loyalty. (ii) The service quality a significant effect on customer loyalty. (iii) affect customer satisfaction has on an effect customer loyalty. (iv) The quality of the service a significant effect on customer loyalty through customer satisfaction. Keywords : quality of service , customer satisfaction and loyalty , servqual models, Islamic microfinance institutions .